TRANSLATION TECHNIQUES OF THE COMPLEX SENTENCES IN BILINGUAL TEXTBOOK BIOLOGY 1 FOR SENIOR HIGH SCHOOL YEAR X PUBLISHED BY YUDHISTIRA (English Dapartment, Faculty of Languages and Arts, Universitas Negeri Semarang, 2013)
This final project was a study which analyzed the use of translation techniques in the bilingual textbook BIOLOGY 1 for Senior High School Year X Published by Yudhistira. The study was done qualitatively. The data were collected by selecting the complex sentences found in chapter five and six. After that, I analyzed and classified the translation techniques used based on Molina and Albir’s classification (2002). Next, the data were counted in order to find the dominant translation techniques. At last, based on the experts, the rendering of meaning from each complex sentence were counted. The result of the study showed that there were 113 complex sentences found in chapter five and six. There were only nine translation techniques, they were literal translation, borrowing, adaptation, reduction, particularization, amplification, generalization, transposition, and description. The rendering of meaning of the 113 sentences was mostly good. 90 sentences (79.64 %) were categorized as good by both experts. From the result, it can be concluded that literal translation dominated the translation techniques used by the translator. Although only 90 sentences (79.64 %) were categorized as good by both experts, the whole sentences can be understood easily because there were no deviated meaning.